Characterization of Devcon Plastic Steel Adhesive on Mild Carbon Steel Steel - Viktor Malau; H Hadromi (Forum Teknik, 2003)
The objective of this research is to characterize  mechanical  and physical behaviors  of adhesives bonding (butt and tap joints) on mild carbon  steel. The research  used an adhesive material  of devcon  plastic  steel. Mechanical properties  are tensile  sftength,  shear strength  andtoughness  of the joints.The major parameters of this research  were adherends surface roughness  Ra, adhesive thickness, curing  time and curing  temperature. Surface  roughness of the carbon  steel adherends are Ra = 0,52 pm, 0,76 pt and I,2l 1m' Adhesive  thichtess  varyfrom:  0,03 mm to 0,3 mm and curing time: 1, 2, 3, 4 hours at curing temperatures:  55, 70, 85, 100, 120 and 140 oC. The research  has been conducted  under static loads at room temperature'The results of static loads (tensile and shear loads) show that adhesive thiclorcss and odherends  surface roughness influence signifcantly the strength  and toughness  of the joints'An increase  in the adherends  surface roughness  will increase  adhesive  strengths. For certain surface  roughness,  the joints  have an optimunt  adhesive thiclorcss  that produces a strength  and toughness maximum.  Heat lreatntent of the joints at curing temperature for certain  curing  timeinfluences  significanlly  shear stresses. An increase  of curing time will increase  shear stresses' At certain  surface roughness  and curing time (for example:  Ra :  0,76 pn and curing time = 4 hours), this research  shows  that the joints have an optimum  curing temperature. Specimenscured at elevated temperqture  show generally  the increasing  strength, however  there is an optimum  temperature where cure exceed this temperature the strength begins decrease. idhesives bonding failure of butt joints are generally cohesive  and lap joints have a mixed failure cohesive and adhesiveKeywords:  adhesive  bonding, mild carbon steel, devcon plastic steel, static load, butt joints.